Social Network Accelerates to Strengthen the Relationship between Teachers and Their Students - Hachem AlaouiHaroun, Moulay; Hachem, El-Kaber; Ziti, Cherif; Bassiri, Mustapha; Lu, Joan (International Journal of Engineering and Technology, 2018)
To make sure that relationship can play an important role in building community as well as knowledge; this article is going to highlight the relationship between teacher-students, teacher-teachers, and student-students by using communitiesâ€™ detection in social network, and this is done by calculating betweenness for all edges and applying the edge removal approach. This paper will make a bridge between the students and the teachers to decide whether this interaction helps to encourage and increase the level of students as well as the teacher performance.Â